Growth Factor-Loaded Mesoporous Silica Particles, Incorporated in Electrospun PCL Fibres, Provide Topographical and Chemical Cues for Tendon Tissue Engineering - Citro, Vera; Clerici, Marta; Shephard, Matthew T.; Dale, Tina P.; Boccaccini, Aldo R.; Forsyth, Nicholas R. (Advanced Materials Technologies, 2025)
This study develops a biomaterial-based strategy to address challenges in controlled growth factor delivery for tenogenic differentiation of mesenchymal stromal cells (MSCs) and tendon stem cells (TSCs). The 20% polycaprolactone (PCL) fibres, electrospun from acetic acid (AA) or formic acid:acetic acid (FA:AA) solutions, are loaded with bovine serum albumin (BSA) to evaluate initial protein-solvent interactions. SEM characterization demonstrated that fibres from AA has larger diameters (391 ± 0.2 nm) than those from FA:AA (282 ± 0.5 nm), with a further increase in diameter upon BSA incorporation. ATR-FTIR analysis confirmed successful protein loading but associated structural changes, particularly in AA fibres. Mesoporous silica nanoparticles (MSNs) are then optimized to encapsulate the model biomolecules BSA, lysozyme, and GDF-7, achieving high encapsulation efficiencies (80–100%) and sustained release due to electrostatic affinity. The MSNs, incorporated into aligned PCL fibres, better protect biomolecule stability and demonstrate uniform distribution, confirmed by SEM-EDS. Functional cell-based assays reveal good cell viability and metabolic activity for MSCs and TSCs cultured on the fibres, further enhanced under physoxic conditions (2% O₂). The scaffold, integrating aligned fibres and MSNs, provides a biomimetic 3D structure for controlled cell alignment and tissue formation. This system offers tuneable drug delivery and shows potential as an autograft alternative for tendon regeneration.
CRIS-Team Scopus Importer:2025-04-25
Keywords: drug delivery system; electrospinning; mesenchymal/stromal stem cells; mesoporous silica nanoparticles; tendon progenitor stem cells; tendon tissue engineering